(untitled) (Journal of the College of Basic Education, 2024)
The current research aims to reveal the types of design techniques and aesthetic features in the implementation of artistic works .the works of the students of the Department of family education and artistic professions for the academic year 2023-224 were identified, and then the terms contained in the title of the research were determined.In the second chapter, we look first at the design techniques and then the aesthetic features . Indicators of the theoretical framework . In the third chapter, the research methodology follows the description, analysis and identification of the society . Where the researcher chose ( 3) a work of art from the indigenous community intentionally because it fits the requirements of the current research by 5%, the researcher built the analysis tool and verified the honesty and consistency by presenting it to a group of experts and after completing the analysis, the results of the researcher showed that the design techniques show their effectiveness in artistic works in an elaborate manner, but the results are achieved through the mechanism of contemporary technologies.And the aesthetic value is achieved in a work of art only by the action of various techniques such as drawing, calligraphy, shapes and symbols .And this view we find in the success of the specificity of the work of art on an aesthetic level, And beauty is not fully realized unless these elements are realized.Then conclusions, recommendations and the most important proposals to carry out the following studies :modern technologies and the mechanism of their interactive production in linear panels .The diversity of technique and materiality in contemporary plastic arts. Then the most important sources used in the research .And the analysis form